Cranberry extract for urinary tract infection treatment in pregnancy: A systematic review - Hakim, Rahmawati Abdul; Putri, Dhian Eka; Rahajeng (Universitas Airlangga, 2025)
HIGHLIGHTS Cranberry represents a promising and effective alternative for both the treatment and prevention of urinary tract infections during pregnancy. Cranberry acts by inhibiting bacterial adhesion to the urinary tract epithelium and exerting direct antibacterial activity. ABSTRACT Objective: Urinary tract infections (UTIs) represent the second most common infectious disease worldwide, affecting nearly 150 million people annually. Owing to anatomical and physiological alterations, UTIs are especially frequent during pregnancy, manifesting with symptoms including dysuria, cloudy urine, increased urinary frequency, and occasionally hematuria. Recurrent UTIs are defined as two or more episodes within six months or three episodes within a year. Cranberries are widely recognized for their potential in preventing UTIs during pregnancy. Their protective action involves blocking the adhesion of uropathogenic bacteria to the urinary tract epithelium, a process mediated by phenolic compounds and A-type proanthocyanidins (PACs). Materials and Methods: In this systematic review, the authors searched PubMed, ScienceDirect, ResearchGate, and Google Scholar for eligible articles published from 2013 to 2024. The search strategy employed Medical Subject Headings (MeSH) and keywords pertaining to Cranberry Extract/Juice and UTI Assessment Methods in Pregnancy. Search expressions were adapted to the specific requirements of each database to optimize retrieval precision. All identified studies were assessed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Of the 30 studies included, a daily administration of 500 mg cranberry extract over six months exhibited notable effectiveness as an alternative therapeutic approach for UTIs in pregnancy. Conclusion: Cranberry (Vaccinium macrocarpon) extract prevents UTIs by impeding bacterial adherence and exerting antibacterial properties. This review supports cranberry as a promising and safe alternative for UTI prevention and management in pregnancy, appropriate for routine daily use.